Influence of the modes of shaping of sand-resin shellis on quality of the produced castings - V. Yu. Kulikov; S. S. Kvon; T. V. Kovalyova; E. P. Shcherbakova; E. N. Eremin (Литьë и металлургия)
Resin in sand-resin mixes in the course of heating at production of casting shell molds undergoes changes of a state: solid – liquid – solid. For the purpose of increase in durability and decrease in contents of binding (pulverbakelit) in mix when forming a shell, along with thermal influence, the static pressure, the resines changing in compliance with change of aggregate state was used. Basic pressure is 0.25 MPas and moves through a press plate right after filling of mix on heated up to 230 °C model plate. In 10 seconds pressure increases up to 0.35 MPas. And in 10 seconds pressure goes down to 0.2 MPas. It is experimentally defined that the castings received in the shell forms made with use of variable pressure have the minimum and uniform internal tension. Also researches showed that such castings have high purity of a surface (Rz 70–80) and lack of internal defects.